Penerapan Manajemen Keuangan dan Digital Marketing pada Pelaku Usaha Rengginang di Desa Kunjir - Fitra Dharma; Yenni Agustina; Andi Windah (Jurnal Nusantara Mengabdi, 2021)
Purpose: The PkM team took the initiative to carry out service activities for the Rengginang business group to improve the skills and insights of partners in preparing financial reports and e-marketing for Minan Rengginang business actors. Method: This service activity involves the Rengginang Minan business group as a partner of this service activity. The methods used in this activity include cognitive, persuasive, and effective ways. Result: The outcome of this activity is an increase in the participants' abilities and knowledge. Conclusion: This activity positively affects the participant group's skills, knowledge, and income.